1994
DOI: 10.2337/diacare.17.10.1172
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors For Distal Symmetric Neuropathy in NIDDM: The San Luis Valley Diabetes Study

Abstract: Worse glycemic control and insulin use were independently associated with neuropathy in people with NIDDM. Whether insulin use represents another marker for severity of the metabolic disturbance or is an independent risk factor for neuropathy requires further study. We could not confirm associations of neuropathy with height, with nephropathy, or with retinopathy, independent of duration of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 22 publications
8
59
1
2
Order By: Relevance
“…Finally, Young et al showed a higher grading of retinopathy for those consuming more than ten alcoholic drinks per week compared with those drinking less than ten drinks per week [9]. For neuropathy, Franklin et al observed an odds ratio of 0.71 for moderate consumers of 0 to 20 g per week, which was similar to our results [10]. Tesfaye et al [11], on the other hand, did not find an association, but detailed results of this analysis were not reported.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, Young et al showed a higher grading of retinopathy for those consuming more than ten alcoholic drinks per week compared with those drinking less than ten drinks per week [9]. For neuropathy, Franklin et al observed an odds ratio of 0.71 for moderate consumers of 0 to 20 g per week, which was similar to our results [10]. Tesfaye et al [11], on the other hand, did not find an association, but detailed results of this analysis were not reported.…”
Section: Discussionsupporting
confidence: 90%
“…Of the invited patients, 85% took part in the study. Patients were stratified by sex, age (15-29, 30-44 and 45-60 years) and duration of illness (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), ≥15 years) before ten patients were randomly selected from each stratum. Ethics committee approval was obtained at each centre and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was a drop in the 61-70 years age group and the reason was not known. As compared to the findings of previous studies, in our study, the prevalence of PIN increased as the age advanced, irrespective of the diabetic status [1][2][3][4][5][6][7][8][9]16,20,21]. The attribution of the increase in age for PIN may be because of the decreased nerve fibres, a reduction in the nerve diameter and changes in the fibre membrane and the conduction velocity {(Huang CR et al,) [22],(Chu NS et al,) [23].…”
Section: Discussionsupporting
confidence: 61%
“…However, studies assessing the effects of exercise training in long-standing, insulin-treated, T2D patients with complications are generally lacking. The latter is partly due to the many difficulties encountered when trying to define an appropriate exercise programme for these patients, who generally suffer from substantial weight gain (5), exercise intolerance and diabetic polyneuropathy (6)(7)(8). The level of diabetic polyneuropathy also appears to be associated with general muscle weakness (9,10), impaired physical performance (11), poor glycemic control (12) and a high cardiovascular risk profile (13).…”
Section: Introductionmentioning
confidence: 99%